507 - Stressful past events and emotional intelligence as predictors of Successful aging. (October 2021) - Buedo-Guirado, Cristina; Dumitrache, Cristina G.; Rubio, Laura
Abstract: Objectives: It has been widely demonstrated that recent stressful events could impact wellbeing, nevertheless it is not clear whether stressful situations experienced in the pastand the internal resources used to deal with them can also influence older adult's well- being. The purpose of this study was to evaluate the influence of stressful past events andemotional intelligence on negative affect, and to determine whether negative affect is related to older people's wellbeing. Method: The Aging in Spain Longitudinal Study, Pilot Survey (ELES-PS) database wasused. The sample comprised 1747 participants (55.9% women), with ages between 50 to98 years-old ( M = 66.2, SD = 10.6). Stressful past events were evaluated with a list of tenstressful events developed by the project team. Three items of the Trait-Meta-Mood scalewere used to assess emotional intelligence. In order to evaluate negative emotions, the PANAS scale of negative experience was used. Finally, life satisfaction was assessed using the Personal Wellbeing Index. Results: The results of the SEM model indicated that emotional intelligence predicted negative affect, and this in turn was related to participants wellbeing. However past stressful events showed no effect on either the emotional intelligence or on participants' negative affect. Age was used as a control variable and influenced negative affect but didnot impact stressful past events. Discussion: Internal resources such as emotional intelligence appears to be more important than stressful past events in predicting successful aging.